Validation of a newly developed immunoassay for TDP-43 in human plasma - Sayo Matsuura; Harutsugu Tatebe; Makoto Higuchi; Takahiko Tokuda (Heliyon, 2024)
The level of TAR DNA-binding protein 43 (TDP-43) in human blood was reported to have potential for use as a specific fluid biomarker, which represents disease-specific pathologies, for TDP-43 proteinopathies, including amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD), which involves the aggregation and deposition of TDP-43 in the nervous system. However, at present, no reliable immunoassay can precisely quantify TDP-43 in human plasma and detect the difference in plasma TDP-43 levels between patients with ALS and controls. We recently developed a novel ultrasensitive immunoassay to quantify TDP-43 in human plasma, and in this study, we analytically validated this assay for application as a diagnostic biomarker for TDP-43 proteinopathies. The novel TDP-43 assay was assessed for the limit of detection, lower limit of quantification, intra- and interassay variation, linearity, parallelism, and analytical spike recoveries. Additionally, 17 pilot plasma samples obtained from patients with ALS and age-matched controls were analyzed using the assay. Our novel TDP-43 assay showed sufficient analytical performance to quantify TDP-43 in human plasma, with high sensitivity (LOD and LLOQ of 0.109 and 0.759 pg/mL, respectively) and high intra- and interassay precision (%CV) below 15 %. The experimental results for spike recovery, parallelism, and dilution linearity were also acceptable. In addition, despite a small sample size, significant differences in the plasma levels of TDP-43 were found between patients with ALS and controls (ALS, 66.63 ± 20.52 pg/mL; control, 42.70 ± 23.06 pg/mL, p = 0.0330). These results support that our novel TDP-43 assay is a reliable and innovative method for the quantification of TDP-43 in human plasma and can be a potential blood-based biomarker for the diagnosis of TDP-43 proteinopathies. Further large-scale studies are warranted to validate its usefulness.